Initiatives for immune-related adverse events by the outpatient pharmacist clinic - Hamatake, Kiyonori; Kojima, Kazuaki (Trends in Immunotherapy, 2022)
Early detection is the key in managing side effects because immune-related adverse events (irAEs) are becoming more serious, and their onset time differs. In our hospital, we conducted an outpatient pharmacist clinic for early detection of irAEs by self-care practice for the cases of immune checkpoint inhibitor administration. As a result of a retrospective survey of 207 cases, the percentage of irAEs found by pharmacist’s suggestion of the outpatient pharmacist clinic increased over time, and a high detection ratio was obtained even for irAEs with a late onset time. The incidence of serious irAEs was higher than that in the immediate post-marketing surveillance, and different factors were considered. Although there were some problems, the outpatient pharmacist clinic had a certain effect.